Prevalence of Salmonella sp. on Hatched Failure of Eggs and One Week's Duckling at the Hatchery Center for Alabio Duck in the District of Hulu Sungai Utara South Kalimantan - . Istiana (Media Veteriner, 1998)
Six hundred and sixty five eggs of hatched failure and 150 of ducklings, from the hatchery of Alabio duck at the District of Hulu Sungai Utara (HSU), South Kalimantan, were examined for Salmonella sp. The results showed that 45 samples of eggs (6.8 %) and 18 samples of ducklings were positive to Salmonella sp (12 %). The serotipe of Salmonella sp. from eggs samples were 17 isolates of S. typhimurium (2.6 %),26 isolates of S. sentenberg (3.9 %), 1 isolate of S. hadar (0.2 %) and 1 isolate of S. virchow (0.2 %); and from duckling samples there are 5 isolates of S. typhimurium (3.3 %), 4 isolates of S. senftenberg (2.7 %), 5 isolates of S. hadar (3,3 %) and 4 isolates of S. virchow (2,7 %).Key words: Salmonella sp, hatchery, Alabio duck